2021
DOI: 10.48550/arxiv.2104.00464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved Image Generation via Sparse Modeling

Abstract: The interest of the deep learning community in image synthesis has grown massively in recent years. Nowadays, deep generative methods, and especially Generative Adversarial Networks (GANs), are leading to state-of-the-art performance, capable of synthesizing images that appear realistic. While the efforts for improving the quality of the generated images are extensive, most attempts still consider the generator part as an uncorroborated "black-box". In this paper, we aim to provide a better understanding and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…For example, Mahdizadehaghdam et al (2019) exploits patch-based sparsity and takes in a pre-trained dictionary to assemble generated patches. Ganz & Elad (2021) explores convolutional sparse coding in generative adversarial networks, arguing that the generator is a manifestation of the convolutional sparse coding and its multi-layered version synthesis process. Both methods have shown that using sparsity-inspired networks improves the image quality of GANs.…”
Section: Connections To Related Workmentioning
confidence: 99%
“…For example, Mahdizadehaghdam et al (2019) exploits patch-based sparsity and takes in a pre-trained dictionary to assemble generated patches. Ganz & Elad (2021) explores convolutional sparse coding in generative adversarial networks, arguing that the generator is a manifestation of the convolutional sparse coding and its multi-layered version synthesis process. Both methods have shown that using sparsity-inspired networks improves the image quality of GANs.…”
Section: Connections To Related Workmentioning
confidence: 99%